Marvel action. Spider-Man. Bad luck. Book 3 - Dawson, Delilah S (Marvel action., 2020)
Peter, Gwen, and Miles have learned to work together, but a sinister new enemy is about to tear them apart in this middle-grade-friendly graphic novel! After a devastating encounter with the Black Cat and her bad luck powers, the Spidey team is down on their luck and at each other's throats. Will Peter, Miles, and Gwen learn to overcome their bad luck and work together again, or is this the end of the line for the Marvelous Spider-Trio?